Shape Matters: Comprehensive Analysis of Star-Shaped Lipid Nanoparticles - Cao, Shuwen; Liu, Xiaodi; Li, Xiuling; Lin, Chunhao; Zhang, Wenyue; Tan, Chee Hwee; Liang, Shunung; Luo, Baoming; Xu, Xiaoding; Saw, Phei Er (Frontiers in Pharmacology, 2020)
The research of lipid nanoparticles (LNPs) has been ongoing for more than three decades, and more research are still being carried out today. Being the first FDA-approved nanomedicine, LNPs not only provide various advantages, but also display some unique properties. The unique lipid bilayer structure of LNPs allows it to encapsulate both fat-soluble and water-soluble molecules, hence enabling a wide range of possibilities for the delivery of therapeutic agents with different physical and chemical properties. The ultra-small size of some LNPs confers them the ability to cross the blood brain barrier (BBB), thus obtaining superiority in the treatment of diseases of the central nervous system (CNS). The ability of tumor targeting is one of the basic requirements to be an excellent delivery system, where the LNPs have to reach the interior of the tumor. Factors that influence tumor extravasation and the permeability of LNPs are size, surface charge, lipid composition and shape. The effect of size, surface charge and lipid composition on the cellular uptake of LNPs is no longer recent news, while increasing numbers of researchers are interested in the effect of shape on the uptake of LNPs and its consequential effects. In our study, we prepared three star-shaped LNPs (LNSs) by mixing Phosphatidylcholine (PC) with different backbone lengths (C14:C4 or C16:C6 or C18:C8) at a 3:1 ratio. Although several star-shaped nanocarriers have been reported, this is the first reported LNS. These LNSs were proven to be safe, similar in size with their spherical controls (~100 nm), and stable at 37 ℃. The release rate of these LNSs are inversely related to the length of the lipid backbone. Most importantly, these LNSs exhibited greatly enhanced cellular uptake and in vivo tumor extravasation compared with their spherical controls. Based on the different uptake and pharmacokinetic characteristics displayed by these LNPs, numerous route formulations could be taken into consideration, such as via injection or transdermal patch. Due to their excellent cellular uptake and in vivo tumor accumulation, these LNSs show exciting potential for application in cancer therapy.